A structural design comparison of metallic and composite aircraft pressure retaining doors - Liu, Hongfen (Cranfield University, 2012)
The pressure retaining door is obviously a sensible part of an aircraft, and the design criteria is much more critical than for the fuselage, so a problem caused by this critical criteria is the heavy weight of the door structure because it should be strong enough to withstand loads and stiff enough to meet the sealing requirements. In spite of the pressure retaining door being so important, it is difficult to find design references. So, in this thesis, the pressure retaining door is investigated first, and then a typical structure of a type A door is selected as the study case using both metallic and composite material, in order to generate a standard method for door structure design, and to identify the key factors which can affect the structure weight. The study indicates that the structure weight of a type A door can be kept in a range for different combinations of beams and stringers, and the composite door structure can be 20% lighter than the metallic door while the stiffness of the two doors remains similar. It is found that the skin contributes much more weight to the door structure than other components and the skin thickness is affected by the short edge of the skin panel divided by beams and stringers. The results also found that it is much more serious when the end stop fails than when the middle stops fail. Therefore, it appears that the composite door is a good material as an alternative to aluminium. Also the method of door structure design is reasonable for the composite door, although it would be better to consider the stiffness of beams while in the theory design period. Besides IRP, the Group Design Project (GDP) is another important part of the MSc study; it lasts nearly half a year and we complete the Fly-wing concept design. The main contribution of the author to the GDP is the arrangement of doors, and also includes the family issues, cabin layout arrangement and a 3D model construct, which can be seen in APPENDIX B. According to the GDP work, I will have broadened my professional knowledge and will have an overall view of aircraft design.
Keywords: Pressure retaining doors; composite; structure; weight